Terapi Murottal dalam Mengatasi Gangguan Pola Tidur pada Pasien Lansia - Dayuningsih Dayuningsih; Meria Woro Listyorini; Adolfina Tandilangan; Koko Wahyu Tarnoto; Rita Setianingrum (Journal of Telenursing (JOTING), 2023)
This study aims to determine murottal therapy in treating sleep pattern disorders in patients. This research method uses quantitative research with a quasi-experimental research design. The results of research using the Wilcoxon test showed that the P-value was 0.000. Conclusion: There is an influence on the sleep quality of older people after listening to the Murottal Al-Qur'an. The duration providing Al-Qur'an or sound therapy for 15-30 minutes can improve the quality of older people's sleep comfort and increase the relaxation effect. Keywords: Sleep Disorders, Elderly Patients, Murotal Therapy